Sesquiterpene Content Analysis of Agarwood Inoculated Using The Simpori Technique - Pratiwi, Dian; Wahyuni, Resti (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2025)
Agarwood is a resin formed in plants that belong to the Thymelaeaceae family, including Gyrinops Versteeg, as a result of damage or microbial infection. The content of sesquiterpenes in both the wild and cultivated agarwood indicates its quality. Nevertheless, information regarding the comparison between the content has not been provided. This study aimed at identifying the sesquiterpenes in G. versteegii inoculated using the simpori technique with various dosages of inoculants (3; 9; and 18 mL/porous nail) and harvested at 18 months after inoculation. The harvested agarwood was extracted using n-hexane solvent. The chemical compositions were subsequently analyzed using the GC-MS. Compounds with a similarity index above 80% were analyzed, including their presence and percentage in the agarwood. The statistical significance test was carried out with a 5% level of significance. The Kruskal-Wallis test showed a P-value <0.05, indicating the significant differences between the inoculant dosages on the percentage of sesquiterpenes. Agarwood with F. solani at a dosage of 9 mL/porous nail shows the best result with a Mean Rank of 16 and 23.69% of sesquiterpenes. It contains aromadendrene; α-selinene; (1aS,4aS,8aR)-4a,8,8-trimethyl-2-methylene-1,1a,2,4a,5,6,7,8-ctahydrocyclopropa[d]naphthalene; 6-Methyl-2-(4-methylcyclohex-3-en-1-yl)hepta-1,5-dien-4-ol; alloaromadendrene; and eremophilene. Therefore, this dosage is recommended for optimizing agarwood production.